THE STUDY OF EXTRAGALACTIC SOURCES 3C 446 AND 3C 345 WITH USING THE SINGULAR SPECTRUM AND WAVELET ANALYSIS - Donskykh, G. I.; Ryabov, M. I.; Sukharev, A. L.; Aller, M. F. (Одеські астрономічні публікації, 2016)
We investigated the data of monitoring of flux density of extragalactic sources 3С446 and 3C345, which was held on 26-meter radio telescope of University of Michigan at frequencies 14.5, 8 and 4.8 GHz. The data of observations were investigated using singular spectrum analysis and wavelet-analysis. According to the results of wavelet analysis for each year of observations, graphics of “spectra periods” were built to determine the contribution of individual periods in the activity of the radio source. The results obtained with two different methods showed a good correlation between them. For a long time component of the flux the periods of ~ 5 – 9 years were found. For short term components the periods of ~ 1 – 4 years are presented. The results obtained using two different methods were compared with VLBI radio maps, which were obtained by the program MOJAVE. The changes of periods over time are associated with certain physical processes in the system "core – accretion disk – jet" and with appearing of new bright components (knots) in the jet